2021
DOI: 10.1021/acs.analchem.0c03848
|View full text |Cite
|
Sign up to set email alerts
|

Representing the Metabolome with High Fidelity: Range and Response as Quality Control Factors in LC-MS-Based Global Profiling

Abstract: Liquid chromatography–mass spectrometry (LC-MS) is a powerful and widely used technique for measuring the abundance of chemical species in living systems. Its sensitivity, analytical specificity, and direct applicability to biofluids and tissue extracts impart great promise for the discovery and mechanistic characterization of biomarker panels for disease detection, health monitoring, patient stratification, and treatment personalization. Global metabolic profiling applications yield complex data sets consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…To facilitate quality assessment and pre-processing, a pooled QC sample was prepared by combining equal parts of each study sample and analysed periodically among study sample analyses. In addition, for assessment of analyte response, 16 a series of QC sample dilutions was created (10 × 100%, 5 × 80%, 3 × 60%, 3 × 40%, 5 × 20%, 10 × 10%, 10 × 1%) and analysed at the start and end of each set of sample analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate quality assessment and pre-processing, a pooled QC sample was prepared by combining equal parts of each study sample and analysed periodically among study sample analyses. In addition, for assessment of analyte response, 16 a series of QC sample dilutions was created (10 × 100%, 5 × 80%, 3 × 60%, 3 × 40%, 5 × 20%, 10 × 10%, 10 × 1%) and analysed at the start and end of each set of sample analyses.…”
Section: Methodsmentioning
confidence: 99%
“…38 Furthermore, by diluting the SR across a range of concentrations to form a set of "dilution series" QC samples, features can also be assessed for how well they are captured with linear dynamic range of the instrument, and for the proportionality of their response to dilution. 5 The SR also forms the basis of pre-processing steps such as batch and run-order correction (see data extraction and pre-processing methods section below).…”
Section: Quality Controlmentioning
confidence: 99%
“…4 However, the resulting datasets are large and complex, typically containing tens of thousands of variables ranging in measurement quality and exhibiting a high degree of redundancy. 5,6 Consequently, biological interpretation of global profiling data is fruitless without considerable effort toward transforming analytical data into biochemical knowledge. This represents a substantial barrier to the success of LC-MS-based metabolomics in clinical and translational research.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the work of Broadhurst et al, the authors did not advise the use of pooled QC serial dilution to filter data based on correlations, since it does not consider a non-linear response, but they mentioned that further work is required to extend the use of this approach [ 122 ]. A recent application of the QC dilution series and advanced filtering proposed by Sands et al showed that dilution QC series, besides its challenges (e.g., poor representation of low abundant metabolites, correct models for a response, account for matrix effects), can be used to estimate the linear range and analyte response and improve the data quality of global metabolic studies [ 123 ].…”
Section: Quality Management Systemmentioning
confidence: 99%